Peningkatan Penjualan Melalui Strategi Sistem Bundling Produk Pada Kelompok Tani Hutan (KTH) “Rukun Maju Sejahtera” - Livia Marcella Devani; Dona Wahyuning Laily (Jurnal Informasi Pengabdian Masyarakat, 2023)
Community Service activities are carried out with the aim of assisting the actors of the Rukun Maju Sejahtera Forest Farmers Group in increasing knowledge and abilities related to the promotion strategy of coffee products using a bundling system so as to optimise the sale of coffee products with other agricultural products owned by the Rukun Maju Sejahtera Forest Farmers Group). The method used in this activity is a participatory approach with several stages as follows: 1) Preparation and planning stage, 2) Activity implementation stage, 3) Evaluation and monitoring stage, 4) Reflection stage. Respondents who participated in this community service activity were the actors of the Rukun Maju Sejahtera Forest Farmers Group. The results of this community service activity are that the Rukun Maju Sejahtera Forest Farmers Group is able to understand and implement a bundling system promotion strategy between coffee products and other agricultural products so as to increase sales.